2011
DOI: 10.1111/j.1365-2648.2011.05762.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership: effect on the job satisfaction of Registered Nurses in a hospital in China

Abstract: The findings indicate that the transformational leadership of nurse managers could have an effect on the job satisfaction of clinical Registered Nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 15 publications
7
46
0
10
Order By: Relevance
“…When analyzing the expectations of nursing teams in face of leadership, the interviewed professionals mentioned that future leaders need to be people who allow frank and open communication, have the capacity to recognize and attend to the needs of teams, know how to give support when needed, and seek harmony in the work environment, working for the union and integration of the group and ensuring the satisfaction of those led. (33) Ten other studies (10,11,(14)(15)(16)18,(20)(21)(22)34) showed positive and significant, direct correlations between the different leadership styles analyzed and job satisfaction; that is, as leadership is exercised and perceived, there is an increase in job satisfaction. The influence of leadership style in the work environment is well-known, because it can lead to synergy or disintegration of teams.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…When analyzing the expectations of nursing teams in face of leadership, the interviewed professionals mentioned that future leaders need to be people who allow frank and open communication, have the capacity to recognize and attend to the needs of teams, know how to give support when needed, and seek harmony in the work environment, working for the union and integration of the group and ensuring the satisfaction of those led. (33) Ten other studies (10,11,(14)(15)(16)18,(20)(21)(22)34) showed positive and significant, direct correlations between the different leadership styles analyzed and job satisfaction; that is, as leadership is exercised and perceived, there is an increase in job satisfaction. The influence of leadership style in the work environment is well-known, because it can lead to synergy or disintegration of teams.…”
Section: Discussionmentioning
confidence: 88%
“…(9) Research developed in China suggested that through transformational leadership, clinical nurses had a higher level of job satisfaction because they felt they could provide more meaningful service to clients and the entire organization. (19) In one of the studies conducted in the United States, transformational leadership had a large and significant impact on the work environment, but for leadership to be performed in nursing units, some aspects needed to be taken into account, such as organizational structures. (12) The point of convergence among the three U.S. surveys was that transformational leadership corresponded to a leadership model that provided an approach to promoting organizational and personal change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herzberg'in çift faktör teorisine göre, çalışma statüsü motive edici faktörlerden biridir ve varlığı kişisel başarı ve doyum sağlamaktadır (Koçel, 2005;Marquis & Huston, 2000). Önceki birçok çalışma sonucu yönetici hemşirelerin klinik hemşirelere göre daha yüksek iş doyumuna sahip olduğunu ortaya koymuştur (Lorber 2012, Uzun 2010, Çelik, Hizar 2012, Liu et al 2012, Faris et al 2010, Wang et al 2012. Farklı olarak, Tovey ve Adams (1999) ve Siqueira et al (2012) yönetici hemşirelere göre klinik hemşirelerin daha yüksek iş doyumuna sahip olduğunu belirlemiştir.…”
Section: Discussionunclassified
“…En el ámbito de la salud, una de las profesiones en las que se ha estudiado ampliamente el impacto de las habilidades de liderazgo en la satisfacción laboral y la calidad de la atención, es la enfermería, en la que el liderazgo transformacional ejercido por los gerentes de servicios de enfermería tiene un gran efecto sobre el nivel de satisfacción laboral de las enfermeras clínicas y sugiere que es esencial para proporcionar programas de capacitación en habilidades de liderazgo para mejorar el conocimiento de las enfermeras gestoras, además de la supervisión, las enfermeras gestoras deben motivar a las enfermeras clínicas para llevar a cabo el trabajo de enfermería clínica con entusiasmo (35) . Las enfermeras tienden a estar más satisfechas con el liderazgo transformacional que con el estilo de liderazgo transaccional, por lo tanto, los gestores de personal de enfermería deben usar el estilo de liderazgo transformacional con el fin de aumentar la satisfacción en el trabajo (36).…”
Section: Liderazgo Y Calidad En El Servicio De Saludunclassified